Multifocal noncontact color imaging for depth-sensitive fluorescence measurements of epithelial cancer - Zhu, Caigang (2014)
We propose a multifocal noncontact setup to perform depth-sensitive fluorescence imaging on a two-layered epithelial tissue model. The combination of a microlens array and a tunable lens enables the depth of the multifocal plane to be conveniently adjusted without any mechanical movement of the imaging lens or the sample. This advantage is particularly desirable in the clinical setting. Results from the phantom study demonstrate that the setup can achieve depth-sensitive color imaging for fluorescence measurements, which is further confirmed by spectral measurements.